Laser-Induced Breakdown Spectroscopy Fundamentals and Applications - Noll, Reinhard; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book is a comprehensive source of the fundamentals, process parameters, instrumental components and applications of laser-induced breakdown spectroscopy (LIBS). The effect of multiple pulses on material ablation, plasma dynamics and plasma emission is presented. A heuristic plasma modeling allows to simulate complex experimental plasma spectra. These methods and findings form the basis for a variety of applications to perform quantitative multi-element analysis with LIBS. These application potentials of LIBS have really boosted in the last years ranging from bulk analysis of metallic alloys and non-conducting materials, via spatially resolved analysis and depth profiling covering measuring objects in all physical states: gaseous, liquid and solid. Dedicated chapters present LIBS investigations for these tasks with special emphasis on the methodical and instrumental concepts as well as the optimization strategies for a quantitative analysis. Requirements, concepts, design and characteristic features of LIBS instruments are described covering laboratory systems, inspections systems for in-line process control, mobile systems and remote systems. State-of-the-art industrial applications of LIBS systems are presented demonstrating the benefits of inline process control for improved process guiding and quality assurance purposes.
Introduction -- Laser-induced breakdown spectroscopy -- Process parameters -- Instrumental components -- Evaporation and plasma generation -- Multiple-pulses for LIBS -- Material ablation -- Plasma dynamics and plasma parameters -- Plasma emission -- Modeling of plasma emission -- Quantitative analysis -- Combination of LIBS and LIF -- Bulk analysis of metallic alloys -- Bulk analysis of non-conducting materials -- Spatially resolved analysis -- Depth profiling -- LIBS instruments -- Industrial applications.
Keywords: Physics; Machinery; Surfaces (Physics).; Physics; Spectroscopy and Microscopy; Atoms and Molecules in Strong Fields, Laser Matter Interaction; Characterization and Evaluation of Materials; Manufacturing, Machines, Tools